Histopathologic features and management of ameloblastoma: study of 20 cases - Martins, Rui Henriques; Sobrinho, Josias de Andrade; Rapoport, Abrão; Rosa, Marilene Paladino (São Paulo Medical Journal, 1999)
BACKGROUND: Odontogenic ameloblastoma (OA) of the jaws is a rare neoplasia of the oral cavity (0.78%) with a 5:1 mandible/maxilla relation, with the molar region and the ascendant ramus being the most affected areas. Comparing our results with the literature demonstrated to us that this tumor may be considered to be a worldwide problem due to the similarity in clinical findings among different ethnic groups CASE SERIES: The purpose of this study of 20 patients with ameloblastoma of the mandible and maxilla diagnosed at the Stomatology and Head and Neck Services of Heliópolis Hospital, São Paulo, Brazil, from 1980 to 1997, was to establish the histopathologic pattern of classification of those tumors through optical microscopy and the relation of this histopathology to therapeutic management. Using the Regeze, Kerr and Courtney classification (1978), we diagnosed follicular tumor in 11 cases, plexiform in 6 cases and unicystic in 3 cases, and performed surgical resection with a safety margin of 1.5 to 3.0 cm in the follicular and plexiform cases and bone curettage in the unicystic cases.